FAK Promotes Early Osteoprogenitor Cell Proliferation by Enhancing mTORC1 Signaling. (5th June 2020) - Qi, Shuqun; Sun, Xiumei; Choi, Han Kyoung; Yao, Jinfeng; Wang, Li; Wu, Guomin; He, Yun; Pan, Jian; Guan, Jun‐Lin; Liu, Fei
ABSTRACT: Focal adhesion kinase (FAK) has important functions in bone homeostasis but its role in early osteoprogenitor cells is unknown. We show herein that mice lacking FAK in Dermo1 ‐expressing cells exhibited low bone mass and decreased osteoblast number. Mechanistically, FAK‐deficient early osteoprogenitor cells had decreased proliferation and significantly reduced mammalian/mechanistic target of rapamycin complex 1 (mTORC1) signaling, a central regulator of cell growth and proliferation. Furthermore, our data showed that the pharmacological inhibition of FAK kinase‐dependent function alone was sufficient to decrease the proliferation and compromise the mineralization of early osteoprogenitor cells. In contrast to the Fak deletion in early osteoprogenitor cells, FAK loss in Col3.6 Cre ‐targeted osteoblasts did not cause bone loss, and Fak deletion in osteoblasts did not affect proliferation, differentiation, and mTORC1 signaling but increased the level of active proline‐rich tyrosine kinase 2 (PYK2), which belongs to the same non–receptor tyrosine kinase family as FAK. Importantly, mTORC1 signaling in bone marrow stromal cells (BMSCs) was reduced if FAK kinase was inhibited at the early osteogenic differentiation stage. In contrast, mTORC1 signaling in BMSCs was not affected if FAK kinase was inhibited at a later osteogenic differentiation stage, in which, however, the concomitant inhibition of both FAK kinase and PYK2 kinase reduced mTORC1 signaling. In summary, our data suggest that FAK promotes early osteoprogenitor cell proliferation by enhancing mTORC1 signaling via its kinase‐dependent function and the loss of FAK in osteoblasts can be compensated by the upregulated active PYK2. © 2020 American Society for Bone and Mineral Research. Abstract : Schematic model of the differential roles of FAK in the cells of osteoblast lineage. The model depicts the mechanisms of FAK action at three distinct stages of osteoblast lineage in which the roles of FAK have been addressed by genetic and pharmacological approaches as well as the respective Cre transgenes used to target Fak, including Dermo1‐Cre (this study), Osterix‐Cre, (10) Col3.6‐Cre (this study), and Col2.3‐Cre . (9) Red ↔ indicates that the loss of FAK in osteoblasts can be compensated by the upregulated active PYK2.